2019
DOI: 10.1101/562322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct current stimulation boosts associative Hebbian synaptic plasticity and maintains its pathway specificity

Abstract: Background: There is evidence that transcranial direct current stimulation (tDCS) can improve learning performance. Arguably, this effect is related to long term potentiation (LTP), but the precise biophysical mechanisms remain unknown. Hypothesis: We propose that direct current stimulation (DCS) causes small changes in postsynaptic membrane potential during ongoing endogenous synaptic activity. The altered voltage dynamics in the postsynaptic neuron then modify synaptic strength via the machinery of endogenou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…Our hypothesis was based on mechanistic differences between the two NIBS techniques. Because tDCS induces sub-threshold shifts in neuronal resting membrane potentials, its ability to elicit enduring effects on behavior are thought to rely upon and leverage Hebbian principles of neuroplasticity [ 72 ]. For this reason, it has been argued that tDCS ought to be most effective when paired with behavioral approaches that engage relevant networks [ 37 , 40 , 42 ], in this case the language network.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis was based on mechanistic differences between the two NIBS techniques. Because tDCS induces sub-threshold shifts in neuronal resting membrane potentials, its ability to elicit enduring effects on behavior are thought to rely upon and leverage Hebbian principles of neuroplasticity [ 72 ]. For this reason, it has been argued that tDCS ought to be most effective when paired with behavioral approaches that engage relevant networks [ 37 , 40 , 42 ], in this case the language network.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is suspected to underlie both novel skill acquisition and recovery of impaired motor skills subsequent to acquired brain injury. Recent in vitro studies have suggested that tDCS can enhance synaptic plasticity in the presence of potentiating neural activity (Kronberg et al, 2017;Kronberg, Rahman, Lafon, Bikson, & Parra, 2019), and this has been recently demonstrated in an in vivo study involving the auditory neurophysiological pathway (Boroda, Sponheim, Fiecas, & Lim, 2020). Thus, given that motor learning involves associative learning and long-term potentiation, and that tDCS may enhance this type of plasticity in the presence of potentiating neural activity, tDCS may be particularly wellsuited to enhancing motor learning.…”
Section: Introductionmentioning
confidence: 98%
“…To improve therapeutic efficacy in people with treatment-resistant depression, some trials have combined tDCS with cognitive training (Brunoni et al, 2014;Segrave, Arnold, Hoy, & Fitzgerald, 2014). It has been suggested that tDCS interacts with ongoing neuronal activity to boost synaptic plasticity within activated regions (Kronberg, Bridi, Abel, Bikson, & Parra, 2017;Kronberg, Rahman, Lafon, Bikson, & Parra, 2019). The administration of behavioural tasks during tDCS may thus be used to pre-activate relevant cortical regions and augment the neuromodulatory potential of tDCS by improving the functional specificity of stimulation (Bikson & Rahman, 2013).…”
Section: Introductionmentioning
confidence: 99%